Management of irritable hip: a review of hospital admission policy. Issue 1 (July 1994) - Taylor, G R; Clarke, N M
Abstract : The case notes of all children admitted during the preceding five years for observation with painful hips (509 patients) were analysed to determine significant diagnostic factors and thus to design and admission policy. Most orthopaedic disorders (62 patients) were apparent on the initial radiographs, with the important exception of osteomyelitis/septic arthritis (21 patients). The remaining 426 patients were diagnosed by exclusion as having an irritable hip. The latter two groups were similar with respect to age, sex, and duration and nature of symptoms. A number of clinical features and laboratory investigations recorded within 12 hours of admission, however, were shown to have significant discriminative value. These were severe spasm, tenderness, pyrexia > or = 38 degrees C, and an erythrocyte sedimentation rate of > or = 20 mm/hour (the white cell count was not significant). Combination of any two of these produced a specificity and sensitivity for sepsis of 91% and 95% respectively (95% confidence interval 0.64 to 0.97). A protocol designed from this data analysis is now being tested and is expected to result in a significant reduction in admission rates.